APPLICATION OF NON-PREEMPTIVE PRIORITY SCHEDULING METHOD FOR WORK ORDER SCHEDULING SYSTEM - Suratun Suratun; Novita Br Ginting; Zulkarnaen Noor Syarif; Ryan Abdul Gofur (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Work order allocation is one of the problems experienced by PT Indomobil Trada Nasional. Companies need tools to make it easier to allocate work orders effectively, namely an optimal work order scheduling system. Work order allocation data for the last three months was 3,817, with 15 technicians. This work order exceeds the company's target, namely to have a difference of 1.2 work orders per technician daily. These work orders have a priority order in their processing. The work order scheduling method used in this research is the non-preemptive priority scheduling method. The non-preemptive priority scheduling method is used because it can determine which work orders are in the queue and ready to be allocated according to the priority order without disturbing work orders that are being worked on when new work orders arrive. The work order scheduling system that was built provides adequate scheduling time and produces a smaller average waiting time, namely 12.97 minutes.   The average waiting time in the scheduling system without priority non-preemptive scheduling is 52.18, and the difference in average waiting time for the 34 existing work orders is 39.12 minutes. Applying the non-preemptive priority scheduling method helps companies allocate work orders optimally.